Code-Switching and Social Identity in NDX A.K.A Songs Entitled “Ngertenono Ati” and “Kimcil Kepolen” - Ni Nyoman Tri Gitayani; Ni Putu Dian Angga Melani (Lingual: Journal of Language and Culture, 2025)
Songs are one of the most effective media for expressing feelings, thoughts, and even social phenomena, as reflected in the choice of vocabulary and language, including the use of language switching. It is described in popular local songs entitled Ngertenono Ati and Kimcil Kepolen, which were sung by NDX A.K.A. This research aims to explore how social representations are expressed through language switching. The data consist of the lyrics of both songs. The analysis was conducted qualitatively by using observation and note-taking techniques, based on Stockwell’s theory of code-switching and Fairclough’s critical discourse analysis. Both songs are primarily in Javanese. In Ngertono Ati Song, there are 23 data involving code-switching from Javanese into Indonesian and English. From these data, six data are classified as intrasentential switching, three data as intersentential switching, and 14 data as tag-switching. The song also employs rhythmic and metaphorical vocabulary to express the feelings of a heartbroken man while simultaneously demeaning a woman perceived as immoral. Meanwhile, in the Kimcil Kepolen Song, 15 data involve switching from Javanese into Indonesian and English. From these data, two data are identified as intersentential switching, 13 data are tag-switching, while intrasentential switching is not found. This song also features rhythmic, metaphorical, and sarcastic vocabulary that presents a portrayal of women as naughty, immoral, and materialistic.